Botswana Print Media and the Representation of Female Victims of Intimate Partner Homicide: A Critical Discourse Analytical Approach. Issue 1 (2nd January 2021) - Bagai, Kelebonye; Faimau, Gabriel
ABSTRACT: Intimate partner homicide (IPH) has become one of the most challenging socio-cultural issues in contemporary Botswana. This paper seeks to examine how female victims of IPH are represented in the Botswana print media. Drawing on data collected from 63 newspaper articles published in four Botswana newspapers between January 2010 and December 2013, the study found that the Botswana print media outlets generally do not represent female victims of IPH in a fair manner as they maintain denigration, degradation and infantilisation of women in their reports. At a macro level, this representation seems to be influenced by an embedded patriarchal ideology. At a micro level, media coverage of intimate femicide tends to sensationalise the causes of passion killings by employing a victim-blaming frame in the representations of the female victims. Using a Critical Discourse Analytical approach, we argue that this mode of media representation does not only maintain the existing gender inequality but also reinforces, perpetuates and naturalises a vicious gender circle. While media reports may have translated the embedded patriarchal ideology to its reporting on the female victims of IPH, we suggest that efforts to achieve gender equality should involve public education including gender-sensitive reporting by public and private print media.